IMPACT OF GLOBALIZATION ON POVERTY IN PAKISTAN - Khadim Hussain; Aizah Yaseen; Nayab Sadaf; Ishrat Zahid (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the effects of globalization on economic poverty in Pakistan. It emphasizes how important it is to comprehend this research issue because poverty vents economic growth and prevents economic growth but also makes life difficult. The analysis takes into account elements including trade openness, FDI, GDP growth rate, population, and inflation using an ARDL model. According to the research, FDI, trade openness, and inflation all have a big impact on poverty. Surprisingly, FDI raises poverty rates, but trade openness mostly benefits the wealthy and widens income disparity by benefiting them. For successful policy-making and the promotion of fair development, it is essential to comprehend the connection between globalization and poverty. To combat poverty and promote equitable economic growth in Pakistan, policymakers must consider domestic and international variables both domestic and international variables into account.